Factors affecting the interest rate policy of commercial banks - Жоламанова, М. (Journal of Economic Research & Business Administration, 2018)
The subject of the flock is conditioned by the need to consider the influence of internal and external factors on the interest rates of banks. The purpose of the study is a comprehensive, reliable study of the main factors influencing the formation of interest rates on the basis of methods of cognition developed in science, as well as obtaining and implementing recommendations of results and conclusions. The choice of the direction of scientific research is related to the need to compile an idea of the features and methods of forming the interest policy of the bank. The research used the method of analysis, synthesis, observation and collection of factual information that allowed studying economic phenomena both in parts (analysis) and in general (synthesis). The article examines the factors influencing the interest rates of commercial banks, which depend primarily on the macroeconomic situation in the country. The National Bank of the Republic of Kazakhstan acting as the main regulator also affects the interest rate policy of banks through the establishment of a base rate. The interest rate also depends on the size of the loan. Also, the value of the interest rate depends on the security of the loan. As a market value, the interest rate depends on the demand and supply of money, the development of the money market, the sources of free money, borrowed funds (their creditworthiness, reliability in repayment of borrowed funds), and other factors. The market rate of loan interest is determined by the interaction of supply and demand in the credit market. The study of the influence of all the above factors on the interest rate of commercial banks forms the basis of this article. The results summed up in the work are of practical importance, and the conducted research has revealed the main factors influencing the interest policy of banks.